Soil fauna changes across Atlantic Forest succession - Correia, Maria Elizabeth Fernandes; Camara, Rodrigo; Ferreira, Claudia Reis; Resende, Alexander Silva; Anjos, Lúcia Helena Cunha dos; Pereira, Marcos Gervasio (Comunicata Scientiae, 2018)
The soil fauna can be used as a bioindicator of soil quality and ecosystem functioning. The present study aimed to assess the effect of the Atlantic Forest secondary succession on the structure and composition of the soil fauna community in Itaboraí, Rio de Janeiro. We selected five areas along a gradient of forest succession: pasture (PA) and four forest fragments (FF1, FF2, FF3, FF4), which are in a toposequence. Thus, we divided the areas in upper, middle and lower thirds and delimitated a transect (20 m) in each third. In the dry season 2010, a metalic square (0.25 m x 0.25 m) was released in five points spaced 5 m apart, in each transect. The soil fauna was manually captured on samples of the litter standing stock and blocks of the topsoil (0.00-0.10 m), circumscribed to the square, in the forest fragments. In PA, we colected only the topsoil blocks. The complexity of the structure and composition of the soil fauna community increased in the topsoil and litter standing stock, along the successional gradient. However, the similarity among the areas was much greater in the litter standing stock, in comparison to the topsoil.